Industry Structure in Developing Company's Long-Term Business Strategy - Vesna Sesar; Krešimir Buntak; Ivana Martinčević; Saša Bogović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Strategic controlling has become an imperative in business planning and determining company's long-term goals. Companies use different managerial tools in their planning process in order to determine possible threats and opportunities in their business environment. The goal of the paper is to present a case study of one pharmaceutical Croatian company using the model INDUSTRUCT, which is utilized for analysing industrial environment, which is, develop based on the Porter's five forces model. Although recent research results show that companies in Croatia use more often operational tools in their business rather than strategic tools this model shows the simplicity of its use and easiness of analyse. Focus of the research is highly competitive rivalry in pharmaceutical industry characterized with the big threats from supplier, buyers, substitutes, as well as newcomers. In such highly competitive industry, companies must constantly rethink their strategies and use tools that will help them detect threats and opportunities hiding in their environment.
Keywords: M21; M49; L10; 330; management strategy; INDUSTRUCT; Porter's five forces; controlling